The image of One Network Bank as projected in its annual reports for the year 2004 and 2005 - Wong, Honey Jane A.
This study was conducted in line with the exploring and understanding the annual report as an important public relations tool in building the image of One Network Bank (ONB) towards its publics. This study aimed to analyze the annual reports of ONB for the 2004 and 2005 and determine the image of the bank for each corresponding year. Guided by the agenda-setting theory, the study employed the five categories for the content of the annual report in identifying the issues raised by the language and visual content of this PR document. In the discussion of the issues, the researcher analyzed the language and visual of the documents as to how these two elements reinforced the prevailing theme of the report. From this analysis, the study inferred the image of ONB for the year 2004 and 2005. After the issues were identified from the content of the document, it was found out that the theme Reaching greater heights to serve rural Mindanao in the 2004 annual report was reinforced by the issues that suggested developing rural Mindanao as the major thrust of ONB's operations and future plan, the banks' lording over the industry as its strength, and the consolidation of its component banks as the factor to the bank's performance for the whole year. While in the 2005 annual report, the theme ONB's growth, Mindanao's development was reinforced by the issues that suggested Mindanao and its development as the company's enduring major thrust, the bank's leadership in the industry and its constant strength, lower income as its weakness points, its philosophy ?pera ng Mindanao, para sa Mindanao?, as the major factor to company performance, and its line of investments as the bank's way of concretizing its future plan. Therefore, it was concluded that the 2004 annual report projected an image of One Network Bank as the leading rural bank in Mindanao, which focuses on Mindanao and its development. It was further concluded that in the first two years of operation as a consolidated unit, ONB was mainly projected as the leading rural bank that is mainly committed to serving and benefiting Mindanao since it is a financial institution that is, itself, created in Mindanao.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication